HUBUNGAN ANTARA PENGETAHUAN DAN SELF EFFICACY DENGAN KESIAPSIAGAAN BENCANA GEMPA BUMI PADA SISWA SMK BINA MANDIRI BOGOR - AGGITA CAHYANI (2020)
Indonesia is a country that located in in the Pacific latitude of the Ring of Fire, constantly at risk of earthquakes, volcanis eruption, floods and tsunamis. Earthquakes is one of most disaster event in Indonesia, will be impact to all aspect of well being, include child and school age. One of the groups that is quite vulnerable to being victims when an earthquake happens is students who are in the school environment. The purpose of this study is to indentify the relationship between knowledge and self efficacy with earthquake disaster preparedness for vocational students in SMK Bina Mandiri Bogor. This research is a quantitative study with cross sectional design. The sampling technique used was simple random sampling with 243 respondents. Data is collected by distributing questionnaires. The results showed the majority of respondents had poor knowledge (84.7%) about disaster knowledge and low levels of self-efficacy (76.2%). Based on the bivariate analysis shown a significant relationship between knowledge and self efficacy with disaster preparedness with P value = 0.000 (P <0.05). Conclusion of this study is that the higher the knowledge and level of self-efficacy, the higher the person's preparedness. The researcher hopes that the school will start to carry out education and disaster simulation routinely, so that students will always be ready when disaster comes.